2023
DOI: 10.3389/fpubh.2023.1068664
|View full text |Cite
|
Sign up to set email alerts
|

Global, regional, and national HIV/AIDS disease burden levels and trends in 1990–2019: A systematic analysis for the global burden of disease 2019 study

Abstract: BackgroundSince the first HIV/AIDS case appeared in 1980s, HIV/AIDS has been the focus of international attention. As a major public health problem, there are epidemiological uncertainties about the future of HIV/AIDS. It is important to monitor the global statistics of HIV/AIDS prevalence, deaths, disability adjusted life years (DALYs), and risk factors for adequate prevention and control.MethodsThe Global Burden of Disease Study 2019 database was used to analyze the burden of HIV/AIDS in 1990–2019. By extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 34 publications
0
15
0
2
Order By: Relevance
“…A systematic analysis of the global burden of disease 2019 study showed the highest health and economic burden of HIV/AIDS in sub-Saharan Africa (attributable to higher behavioural risks, drug use, partner violence and unsafe sex). 1 A scoping review conducted in Latin America involving 196 articles showed a 2.8%–15.2% pooled prevalence of HIV among people who used substances. 2 A United Nations and Drug and Crime report in 2023 showed a rising trend of injecting drug use (IDU) (ie, 13.2 million in 2021 and 11.2 million in 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A systematic analysis of the global burden of disease 2019 study showed the highest health and economic burden of HIV/AIDS in sub-Saharan Africa (attributable to higher behavioural risks, drug use, partner violence and unsafe sex). 1 A scoping review conducted in Latin America involving 196 articles showed a 2.8%–15.2% pooled prevalence of HIV among people who used substances. 2 A United Nations and Drug and Crime report in 2023 showed a rising trend of injecting drug use (IDU) (ie, 13.2 million in 2021 and 11.2 million in 2020).…”
Section: Introductionmentioning
confidence: 99%
“…AIDS, caused by HIV, is the most prevalent immunosuppressive disease and a significant global health challenge that continues to affect and take human lives [ 1 , 2 ]. Globally, an estimated 39.0 million people were living with HIV at the end of 2022, two-thirds of whom are in the WHO African Region [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Global Burden of Disease report indicated that there were 36.85 million cases of HIV/AIDS in 2019, which shows an increment of 307.26/100,000 cases compared with 1990. Similarly, there were 863.84 thousand deaths in 2019 due to HIV/AIDS, which showed an increase of 10.72 deaths/100,000 cases compared with 1990 [ 2 ].…”
Section: Introductionmentioning
confidence: 99%